Revitalizing Performance Management System Using Process, Purpose, Effectivenes Theory and Competing Values Framework at PT Kereta Api Indonesia (Persero) - Kusumowiwoho, Pradipto; Bangun, Yuni Ros; Welly, John (The Indonesian Journal of Business Administration, 2013)
PT. Kereta Api Indonesia is one of Indonesiaâ€™s state owned company which operate in transportation industry. With a series of past failures, such a financial loss in 2007 and 2008, PT. KAI starts to conduct transformation. â€œAnda adalah prioritas kamiâ€ is emerged as a new main slogan followed by â€œ5 nilai utamaâ€ as a new organizational culture. This transformation should be followed by several changes, including performance management system as a support system. Management of PT. KAI may play a role in creating, maintaining, and providing compensation for the efforts and programs to support the implementation of core values.This research used two models study to assess the performance system in the company. First is the theory of process, purpose, and effectiveness to assess the system itself based on those three theories. Second is the competing values framework which is used to assess culture and define proper appraisal system based on three aspects of leadership, effective organization, and TQM. In this final project, the research was carried out through questionnaire. For system assessment, questionnaires were randomly distributed to PT KAI employees in Bandung headquarter, while for cultural assessment was conducted in two divisions, which are marketing and strategic business development division using Organization Culture Assessment Instrument.Â Keywords: PT Indonesia Railway, performance management systems, competing values framework, organization culture assessment instrument